Pengaruh Harga, Kualitas Produk, Citra Merek dan Promosi terhadap Keputusan Pembelian Smartphone Merek Oppo dengan Kepuasan Konsumen sebagai variabel Mediasi(Studi Kasus pada Mahasiswa Universitas Nusa Bangsa) - Saputra, Muhamad Riko Yanwar; Nia Sonani; Rumna, Rumna (IPM2KPE, 2025)
This study aims to analyze the influence of price, product quality, brand image, and promotion on Oppo smartphone purchase decisions, with consumer satisfaction as a mediating variable among students at Nusa Bangsa University. The research method used a quantitative approach with a causal associative approach. The sample consisted of 147 respondents selected using purposive sampling. The research instrument, a Likert-scale questionnaire, was then tested for validity and reliability. Data analysis was performed using multiple linear regression and a mediation test using SPSS version 25. The results showed that price, product quality, brand image, and promotion had a positive and significant influence on purchase decisions. Furthermore, price, product quality, brand image, and promotion also significantly influenced consumer satisfaction. Furthermore, consumer satisfaction was shown to act as a mediating variable in strengthening the relationship between price, product quality, brand image, and promotion on purchase decisions. These findings confirm that a marketing strategy that emphasizes a combination of competitive pricing, superior quality, a strong brand image, and appropriate promotion can increase consumer satisfaction and purchase decisions. Keywords: Price, Product Quality, Brand Image, Promotion, Consumer Satisfaction